PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. PELABUHAN INDONESIA III (PERSERO) TERMINAL PETI KEMAS SEMARANG - Christian Andico; Sudharto Prawoto Hadi (Universitas Diponegoro, 2013)
This research aimed to determine the effect of compensation and work motivation on PT. Pelabuhan Indonesia III (Persero) Terminal Peti Kemas Semarang. The type of research used is explanatory research with 67 respondents taken using a proportionate stratified random sampling technique. Engineering data on this research using interview and questionnaire. The analysis technique using validity test, reliability test, simple linear regression, multiple linear regression, t test and F test with the tools SPSS 20.0. The results showed that compensation effect on employee performance, motivation of work effect on employee performance. Compensation and work motivation are jointly effect on employee performance. Advised to PT. Pelabuhan Indonesia III (Persero) Terminal Peti Kemas Semarang could give money to eat and the appropriate and proper bonuses with time already determined earlier, giving companies a sort of intensive and ongoing training, seminars are themed work motivation, as well as controlling to each employee on the employee’s performance is already done and occasionally provide some sort of briefing directly to each employee who has a low performance so that going forward is expected to reduce the level of misconduct as well as fostering and enhancing employee initiative for finish the job on time.